Jungle warriors from Tobruk to Kokoda and beyond, how the Australian Army became the world's most deadly jungle fighting force - Threlfall, Adrian (Allen & Unwin, 2014)
Jungle Warriors examines the extraordinary transformation that the Australian Army underwent over the course of the Second World War. During this period the Australian Army transformed itself from a military force totally unprepared for conflict of any kind in 1939, into one of the most professional, experienced and highly skilled jungle warfare forces in the world by 1945. Beginning in the interwar years, when the Australian Army was rundown, ill-equipped and dispirited, this book traces the sweeping changes that occurred throughout the course of the war... This book follows the story from Puckapunyal and Ingleburn to Tobruk and Greece, back to Queensland and on to Milne Bay, Kokoda, the Beachheads and final victory in Borneo, Bougainville and New Guinea. The scale of the transition and level of accomplishment by the men of the 2nd AIF will be clear by the end. Instead of a series of disjointed 'snapshots' of Australia's war in the Pacific, a coherent and comprehensive narrative will follow the men of the 2nd AIF from the outbreak of the war in 1939 to the end of hostilities in 1945. How these men became exceptional jungle warriors will be fully explained and fully understood as never before